Sosialisasi dan Praktik Pembuatan Aquaponik Skala Mini Guna Optimasi Pekarangan Rumah Untuk Sedia Ketahanan Pangan - Muhammad Farid Nasrulloh; Ari Dwi Putra; Muhammad Rif’an Hariri; Mochammad Ja’far Sodiq Maksum; Mohammad Faridl Darmawan (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2026)
The condition of Nglele village shows that there is great potential in the yard land that has not been utilized optimally. So far, the fulfillment of community food needs still depends on agricultural products and markets for daily food needs. Food is a basic need for every human being. In addition, there is another problem, namely the lack of public awareness regarding good waste management among the community. The objectives of community service activities in the community partnership program through socialization and practice of making mini-scale aquaponics to optimize home yards for food supplies are as follows: (1) To increase the understanding and skills of the Nglele Village community regarding the use of home yard land, waste management, and basic aquaponic techniques. To encourage people to use yard land. (2) through independent fish and vegetable cultivation. (3) To teach about the management of used gallons to be processed into goods of economic value. To increase public awareness about the importance of protecting the environment and managing natural resources sustainably. The service method used in the implementation of this community service is the Participatory Action Research (PAR). Based on the results of the Community Service Program (KKN-PPM), several things can be identified as follows: This program successfully increased the understanding and skills of participants, especially PKK mothers, about aquaponics. Before the program, only 15% of participants knew the term aquaponics, but after the program, 90% of participants understood it. This activity successfully demonstrated how to convert used gallon waste into productive assets. By utilizing previously suboptimal home yards, participants can produce fish and vegetables to meet family nutritional needs and potentially open up new business opportunities. method.